Constitutionality and legality on the implementation of the day atypical cumulative in mining and no obligation or payment for the work of holidays - Vela Gonzáles, Carlos G. (2016)
The importance of Atypical Cumulative Journey in mining in our country is that it facilitates increased production and uses for this labor force miners to work cycles (also called work systems) consisting of periods cumulative work and are also offset by cumulative periods of rest, but this should be met with various constitutional parameters (1993 Constitution, Constitutional Court rulings and Convention 01 of the International Labour Organization - ILO) as well as various legal parameters (Journey Act and Regulations, Consolidation of Remunerated Breaks and Regulations) and other highly important interpretative parameters (Directives and Reports of the Ministry of Labour - MLEP). To have these parameters cumulative atypical journey in mining will be constitutionally and legally valid.Moreover, after specifying the constitutionality and legality of such work journey, now must define an appearance on labor law that has led to very divergent positions by the labor inspectorate